CONCEPT DEVELOPMENT OF INSTRUMENTATION AND METHODICAL COMPLEXES FOR RESEARCH TECHNICAL STATES COLUMN EXPLOITATION WELLS - Elena V. Belaya; AbdulGapur G. Kerimov; Vyacheslav G. Kopchenkov; Olga Y. Turskaya (Вестник Северо-Кавказского федерального университета, 2022)
In article are considered welling the device on diagnostics of a technical condition casing string (three- dimensional model).